A further note on the alleged Egyptian etymology of Sabaoth - Theis, Christoffer (Vetus Testamentum, 2024)
This note provides further arguments against a proposed Egyptian etymology of the divine name or title צְבָאוֹת (ṣᵉbāʾōt), as initially proposed by Manfred Görg, and expands a recent article by Giuseppina Lenzo and Christophe Nihan.